"I beg you pardon, I never promised you a rose garden" an interpretation of meaning and aesthetic in urban residential landscape. - Ismail, Nor Atiah; Egoz, Shelly; Cushman, Grant; Abd Aziz, Nurul Aqilah (Scottish Group, 2013)
Substantial rural-urban migration in Malaysia in 1971-1975 is underpinned by aspirations for better economic, educational and social opportunities. The shift to an urban area requires adaptation to a totally different environment. The migrants who had earlier lived in squatter settlements continue to practise their local culture and kampong (village) values even after they have been relocated to newly planned residential areas. The responsive cultural landscape characteristics that embodied the residents’ way of life were disapproved of by the Municipal Council as it reflected the image of a blighted land. The Council prefers to develop homogenous residential landscapes mainly for aesthetic values. This research challenges the idea of aesthetic homogenous landscapes in urban residential areas. The qualitative research approach adopted in this research investigates the conflict between cultural meanings and the aesthetic values embedded in medium-cost urban residential landscapes. The findings of this research reveal that the residential landscape is not just another ‘designed space’ to be looked at, it is a ‘living place’ that can help to shape the residents’ identities, to fulfill their aspirations and more importantly, to enable them to live without being alienated. This research’s findings may help relevant government agencies and industry players to better understand landscape issues and community needs in medium-cost housing, rather than just providing a ‘one design fits all’ solution